CCS Research Development and Deployment in a Clean Energy Future: Lessons from Australia over the Past Two Decades. (August 2017) - Cook, Peter J.
Abstract: There is widespread, though by no means universal, recognition of the importance of carbon capture and storage (CCS) as a carbon mitigation technology. However, the rate of deployment does not match what is required for global temperatures to stay well below 2 °C. Although some consider the hurdles to achieving the widespread application of CCS to be almost insurmountable, a more optimistic view is that a great deal is now known about CCS through research, demonstration, and deployment. We know how to do it; we are confident it can be done safely and effectively; we know what it costs; and we know that costs are decreasing and will continue to do so. We also know that the world will need CCS as long as countries, companies, and communities continue to use fossil fuels for energy and industrial processes. What is lacking are the necessary policy drivers, along with a technology-neutral approach to decrease carbon emissions in a cost-effective and timely manner while retaining the undoubted benefits of ready access to reliable and secure electricity and energy-intensive industrial products. In this paper, Australia is used as an example of what has been undertaken in CCS over the past 20 years, particularly in research and demonstration, but also in international collaboration. Progress in the large-scale deployment of CCS in Australia has been too slow. However, the world's largest storage project will soon be operational in Australia as part of the Gorgon liquefied natural gas (LNG) project, and investigations are underway into several large-scale CCS Flagship program opportunities. The organization and progress of the Cooperative Research Centre for Greenhouse Gas Technologies (CO2CRC) Otway Project, which is currently Australia's only operational storage project, is discussed in some detail because of its relevance to the commercial deployment of CCS. The point is made that there is scope for building on this Otway activity to investigate more broadly (through the proposed Otway Stage 3 and Deep Earth Energy and Environment Programme (AusDEEP)) the role of the subsurface in carbon reduction. There are challenges ahead if CCS is to be deployed as widely as bodies such as the International Energy Agency (IEA) and the Intergovernmental Panel on Climate Change (IPCC) consider to be necessary. Closer international collaboration in CCS will be essential to meeting that challenge.